PENGARUH IMPLEMENTASI PERMAINAN SCRAMBLE TERHADAP KEMAMPUAN MENULIS SISWA KELAS IV SEKOLAH DASAR - Evin Dwi Amalinda; Ahmad Nurefendi Fradana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Writing skills are the abilities used to express ideas non verbally. Writing skills at the elementary school level are divided into two, namely beginning writing skills and advanced writing skills. There are several aspects in writing, namely the use of appropriate punctuation, languange structure, spellng, and word choice. Writing skills can be trained and improved through scramble games. The scramble game is a game of random words pr letters which consist of three types, namely word scramble, sentence scramble, and discourse scramble. This game function to improve student’s ability to think quickly and creatively. This research was conducted to find out whether there was an influence of the implementation of the scramble game on the writing abilities of fourth grade elementary school students. The result obtained from the research that has been carried out are that there is a significant influence from the implementation of the scramble game on the writing abilities of fourth class elementary school students.